Y=x2-12x-5

Simple and best practice solution for Y=x2-12x-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Y=x2-12x-5 equation:



=Y2-12Y-5
We move all terms to the left:
-(Y2-12Y-5)=0
We add all the numbers together, and all the variables
-(+Y^2-12Y-5)=0
We get rid of parentheses
-Y^2+12Y+5=0
We add all the numbers together, and all the variables
-1Y^2+12Y+5=0
a = -1; b = 12; c = +5;
Δ = b2-4ac
Δ = 122-4·(-1)·5
Δ = 164
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$Y_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$Y_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{164}=\sqrt{4*41}=\sqrt{4}*\sqrt{41}=2\sqrt{41}$
$Y_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(12)-2\sqrt{41}}{2*-1}=\frac{-12-2\sqrt{41}}{-2} $
$Y_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(12)+2\sqrt{41}}{2*-1}=\frac{-12+2\sqrt{41}}{-2} $

You can always share this solution

See similar equations:

| X^(2)=4-6x | | 15b+50=35 | | 17(5)^x=7(2)^x | | ((5x)/(2))+4=7x | | 4/3x-1+(2x+3)(2x-3)/12-(2x+3)2=2/3x-9x-3/6 | | 4/3x-1+(2x+3)(2x-3)/12-(2x+3)^2=2/3x-9x-3/6 | | 40x+10(1.5x)=1600 | | p+6p?5p=20 | | 4x^2-70x+150=0 | | 2x2+5x-8=0 | | 7x=3x+12=2x+5= | | 7x=3x+122x+5= | | 3/d+2=9 | | 50.?56+x=?12?23 | | 2*(x+8)=20 | | 22*x=226 | | 4n+12+3n=82 | | 2*(x+4)=14 | | 10=90(1/2)^x | | 17–x=9x= | | 5*(x-3)=15 | | 8*(x+2)=48 | | 4x+66=10x+12x= | | 12x-3x-36000=0 | | 0,5*(x-8)=5 | | 5*(x+4)=30 | | 44=2/3x | | n/20=3 | | 0.2x-1.7=0.6x-0.1 | | 13x2+28x+4=0 | | 0.4x-1.5=0.7x-0.6 | | n+28=96 |

Equations solver categories